The socio-cultural implications of glacier retreat demand further attention: a case study from Cerro El Plomo in Santiago, Chile - Altemus Cullen, Kate; Ayala, Álvaro; Spencer, Millie (Frontiers in Earth Science, 2025)
Glaciers provide vital meltwater to rivers and mountain ecosystems and hold profound significance for societies worldwide. Their retreat due to climate change has been well documented, however, research has overlooked the socio-cultural dimensions of their retreat, particularly in the Chilean Andes. We use the case of the retreating glaciers of Cerro El Plomo near Santiago, Chile to call for more collaborative studies between glaciologists, anthropologists, and local communities. The Cerro El Plomo glaciers are arguably the most visible and socio-culturally significant in the Santiago region. Satellite imagery analysis and prior studies show that the total area of Cerro El Plomo glaciers has decreased by 17% ± 6% since 2000 and their mass balance has become increasingly more negative, particularly after the onset of the Central Andes megadrought in 2010. The mountain’s hanging glacier has retreated up the steep bedrock, with many areas of the glacier tongue thinning by 10–20 m from 2017–2022. A literature review indicates that glacier retreat disrupts and may reconfigure long-standing relationships that local groups have with them. These include Andean Indigenous and mestizo peoples for whom glaciers hold deep cosmological significance as part of the Cerro El Plomo apu (sacred protector); mountain guides and arrieros (traditional herdsmen or muleteers) whose social identities and livelihoods are tied to them; and santiaguinos (Santiago residents) who view them as emblems of the landscape and derive from them a sense of place. The retreat of these glaciers presents not only a water security risk, but also important socio-cultural implications that deserve further study.